Purple is part of a rainbow - Kowalczyk, Carolyn; Sharp, Gene, 1923- (New York : Childrens Press, 1985)
Introduces vocabulary and the concept of parts of a whole with examples such as a petal on a flower and a whisker on a kitty.
Booklist.
School Library Journal.
Booklist, November 2005.
School Library Journal, December 1999.
1.1
2.
Keywords: Readers (Elementary).; Whole and parts (Psychology) -- Juvenile literature; Vocabulary; Vocabulary; Readers (Elementary).